Nilai-nilai Pendidikan Islam dalam Tradisi Kelahiran Anak di Sumatra Selatan - Mu'minin, M. Amirul; Karoma, Karoma; Handayani, Tutut (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to reveal the values ​​of Islamic education contained in the tradition of childbirth. This study uses a qualitative approach with a case study method in Sidomukti village, Banyuasin Regency, South Sumatra. The study subjects included parents who had just given birth, community leaders, and religious leaders selected through purposive sampling techniques. Data were collected through in-depth interviews, participant observation, and document analysis. The study had three main findings. First, birth traditions such as aqiqah and naming reflect the values ​​of Islamic education, gratitude to Allah, and a commitment to instilling spiritual values ​​from an early age. Second, the involvement of religious leaders in naming emphasizes the importance of religious guidance in children's education, which is seen as the beginning of the formation of Islamic character. Third, the Thanksgiving event after the aqiqah is a forum for strengthening social ties, delivering religious advice to parents, and strengthening community support in children's education. In conclusion, the birth tradition in Sidomukti is not only a social ritual but also a medium for character and spiritual education based on Islamic values. This study recommends integrating these values ​​into formal and non-formal education curricula to support forming a generation with Islamic character and high spiritual awareness